ANALISA BIAYA RELEVAN UNTUK PENGAMBILAN KEPUTUSAN JANGKA PENDEK PADA PERUSAHAAN KECAP CAP Ã¢â‚¬Å“BAKSO SATEÃ¢â‚¬Â PURWOKERTO - Kristanti, Ika Neni (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2014)
This study aims to analyze the costs relevant to decision making soy products continue the company's plastic packaging ketchup cap "BAKSO satay" Purwokerto The study drew on data in 2010 who suffered losses. Loss was due to higher production costs due to: rising gas prices and soaring oil prices, labor costs need to be given a salary increase and the costs of medical care from year to year increases, the engine was getting old so the ability of the operation is reduced and weakening market demand for soy products plastic packaging. From the results of the study concluded that the company should continue the plastic packaging for soy products if the company will add a stop loss is greater. This can be evidenced by the company discontinue the product if it will experience a loss of Rp. 34.092 million, whereas if you continue to lose Rp. 12.6898 million, and the difference is Rp.21,402,200, - This research method is by way of: interviews, observation, documentation and literature study method. The main results of this study indicate that the company should continue soy plastic packaging products for reasons above.